2014
DOI: 10.3390/ijms150915994
|View full text |Cite
|
Sign up to set email alerts
|

In Silico Discovery of Potential VEGFR-2 Inhibitors from Natural Derivatives for Anti-Angiogenesis Therapy

Abstract: Angiogenesis is the growth of new capillaries from existing blood vessels that supply oxygen and nutrients and provide gateways for immune surveillance. Abnormal vessel growth in term of excessive angiogenesis is a hallmark of cancer, inflammatory and eye diseases. VEGFR-2 (vascular endothelial growth factor receptor 2) dominating the process of angiogenesis has led to approval of therapeutic inhibitors and is becoming a promising target for anti-angiogenic drugs. Notwithstanding these successes, the clinical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(30 citation statements)
references
References 65 publications
0
29
0
1
Order By: Relevance
“…The energy minimization was performed to relax the complex system under 1000 kcal/mol/nm by using the steepest descent method.(J. Li et al, 2014) Afterwards, 100 ps NVT (constant number of particles, volume, and temperature) ensemble stabilized the system at 300 K and subsequently, 100 ps NPT (constant number of particles, pressure, and temperature) equilibration stabilized the system pressure by using coupling reference pressure of 1 bar. Finally, we ran the 10 ns MD simulation with a time step of 2 fs, storing corresponding coordinates every 2 ps.…”
Section: Simulationmentioning
confidence: 99%
“…The energy minimization was performed to relax the complex system under 1000 kcal/mol/nm by using the steepest descent method.(J. Li et al, 2014) Afterwards, 100 ps NVT (constant number of particles, volume, and temperature) ensemble stabilized the system at 300 K and subsequently, 100 ps NPT (constant number of particles, pressure, and temperature) equilibration stabilized the system pressure by using coupling reference pressure of 1 bar. Finally, we ran the 10 ns MD simulation with a time step of 2 fs, storing corresponding coordinates every 2 ps.…”
Section: Simulationmentioning
confidence: 99%
“…These receptors have recently caught the consciousness of the researchers as a stunning target to combat cancer owing to the proper documentation suggesting their over-expression on cancer cells. Number of reports confirm that, Green tea diminish the cell proliferation and promoted to cancer cell for growth inhibition in diverse cancer cells including colorectal, hepatocellular carcinoma cells, SW480 colon cancer cells, SV40 virally transformed WI38 human fibroblasts (WI38VA), prostate cancer, and Ishikawa cells [8][9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 93%
“…115 Such design was based on earlier findings that urea-bearing pyrrolo [ Bao and co-workers identified three potential VEGFR-2 inhibitors (2-4) from the ZINC database through virtual screening and molecular docking analyses. 117 Molecular dynamics simulations demonstrated that these compounds could target VEGFR-2 with similar binding free energy for anitinib (-54.68 kcal/mol). Such results suggested that these compounds would bind to VEGFR-2-like anitinib with similar inhibition and antiangiogenic potency.…”
Section: Recent Progress In the Development Of Vegfr-2 Inhibitorsmentioning
confidence: 98%
“…Bao and co‐workers identified three potential VEGFR‐2 inhibitors ( 2–4 ) from the ZINC database through virtual screening and molecular docking analyses . Molecular dynamics simulations demonstrated that these compounds could target VEGFR‐2 with similar binding free energy for anitinib (–54.68 kcal/mol).…”
Section: Recent Advances In Small‐molecule Antiangiogenic Agentsmentioning
confidence: 99%